1997
DOI: 10.1073/pnas.94.8.4017
|View full text |Cite
|
Sign up to set email alerts
|

KvLQT1, a voltage-gated potassium channel responsible for human cardiac arrhythmias

Abstract: The clinical features of long QT syndrome result from episodic life-threatening cardiac arrhythmias, specifically the polymorphic ventricular tachycardia torsades de pointes. KVLQT1 has been established as the human chromosome 11-linked gene responsible for more than 50% of inherited long QT syndrome. Here we describe the cloning of a full-length KVLQT1 cDNA and its functional expression. KVLQT1 encodes a 676-amino acid polypeptide with structural characteristics similar to voltage-gated potassium channels. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
161
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 26 publications
(23 reference statements)
5
161
0
2
Order By: Relevance
“…However, little is known about whether delayed rectifier K + currents, which are sensitive to volatile anesthetics, is present in the central nervous system. It has been reported that KVLQT1 is strongly expressed in human heart and pancreas (32), and KCNE1 mRNA is abundant in the kidney, submandibular gland, and the uterus (33,34). However, both are hardly expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about whether delayed rectifier K + currents, which are sensitive to volatile anesthetics, is present in the central nervous system. It has been reported that KVLQT1 is strongly expressed in human heart and pancreas (32), and KCNE1 mRNA is abundant in the kidney, submandibular gland, and the uterus (33,34). However, both are hardly expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…There are five known ␣-subunits (K v 7.1-K v 7.5), and the sequence alignment of the hydrophobic regions divides them into two groups, one comprising K v 7.1 and the other K v 7.2 to K v 7.5. K v 7.1 is found in the heart (Yang et al, 1997) and in epithelial tissues (Schroeder et al, 2000b), whereas K v 7.2 to K v 7.5 are expressed primarily in neurons and are therefore collectively referred to as neuronal (Biervert et al, 1998;Singh et al, 1998;Yang et al, 1998;Kharkovets et al, 2000). All K v 7 channels, with the exception of K v 7.5, have been linked with hereditary diseases: K v 7.1 with cardiac long QT syndrome, K v 7.2 and K v 7.3 with benign neonatal familial convulsions, and K v 7.4 with deafness (for reviews, see Robbins, 2001;Gribkoff, 2003).…”
mentioning
confidence: 94%
“…Consistently, both channel proteins contain threonine residues within the pore region at a position that mainly determines sensitivity to external blockade by TEA. While in KCNQ2 a tyrosine residue at this position confers high TEA sensitivity (19,35), other residues may be responsible for the intermediate TEA sensitivity of KCNQ1 and KCNQ4 (6,34). Another nonspecific potassium channel blocker, quinidine, at 300 M blocked KCNQ5 currents by 50%.…”
Section: Cloning and Tissue Distribution Of Kcnq5-a Search Of The Genmentioning
confidence: 99%
“…So far, the KCNQ family consists of four members, all of which are associated with hereditary human diseases. KCNQ1 functionally interacts with KCNE1 (IsK) (2), a small ␤-subunit protein with a single transmembrane domain, to generate the slowly activating delayed rectifier I Ks current of cardiomyocytes (3)(4)(5)(6).…”
mentioning
confidence: 99%